Dampak Kebijakan Program Pemulihan Ekonomi Nasional (PEN) Terhadap Kolektibilitas Kredit Studi Kasus : PT. Pegadaian Area Padang - Rima Fauziatul Husna; Doni Satria (Universitas Negeri Padang, 2023)
This study aims to determine the effect of Customer Characteristics indicators of gender, age, education, marital status, and number of dependents, Business Characteristics indicators of business fields, ownership of business premises, length of business and monthly income, Credit Characteristics indicators of loan value, products, and the installment ratio, as well as the Characteristics of the National Economic Recovery Program (PEN) indicators of restructuring on Credit Collectibility at PT. Padang Area Padang. This research data is based on secondary data on 1,204 active customers of PT. Padang Area Padang on January 23, 2022. By using logistic regression method, the results of this study indicate that the variables of education, trade dummy, flexion dummy, installment ratio, restruk dummy , and lepas restruk dummy have a significant influence on credit collectibility at PT. Padang Area Padang